Leaving Money on the Table: Do Institutional Investors Fail to File Claims in Securities Class Actions? - James D. Cox; Randall S. Thomas (Washington University Law Quarterly, 2002)
Commencing two decades ago, and continuing today, the institutional investor is the most significant focus in reform efforts for securities markets and the American corporation. Whether the question is the type of disclosures that must be made in connection with a public offering, the scope of nonpublic offerings, or making the corporation more responsive to owners, the focus is on the significant trading and ownership interest of institutional investors. As is well understood, such emphasis on financial institutions in reforming corporate and securities laws is based upon their ownership of, and trading in, the stock of publicly held corporations. For example, financial institutions own nearly 50% of the equity securities listed on the New York Stock Exchange (NYSE) and account for approximately 75% of the daily trading volume on the NYSE.4 The ownership and trading percentages are equally high for securities listed on the North American Securities Dealers Exchange (Nasdaq). Though we also champion the vast potential that has been accorded institutional investors, we examine here one area where financial institutions are claimed to be guilty of passivity equal to that of the “small investors”: do financial institutions fail to submit claims for their losses in settled securities class actions? In other words, do institutions frequently leave money on the table that is theirs for the asking?
Keywords: Institutional investments; Class actions (Civil procedure); Securities; Class action settlements; Securities fraud; Securities law